Description of a new distinctive species of Parabetaeus Coutière, 1897 (Decapoda: Caridea: Alpheidae) from the Indo-West Pacific - Anker, Arthur (Zootaxa, 2015)
Parabetaeus acanthus sp. nov. is described based on two specimens from Thuwal, Saudi Arabia, and Madang, Papua New Guinea. The new species is unique within the genus in possessing an anteriorly directed, spine-like tooth on the mid-dorsal line of the carapace, posterior to base of the eyes, and in the stylocerite not reaching the mid-length of the first article of the antennular peduncle. The chelipeds of P. acanthus sp. nov. are variable in size and proportions, as well as in the armature on the finger cutting edges. This cheliped polymorphism appears to be typical to all species of the genus.